Model of Firm Value – Indonesian Stock Exchange Case - Elim, John (International Journal of Economics and Financial Issues, 2019)
Aim of the research is to investigate whether cash dividend tax, institution ownership and retained earning influence on dividend policy and their implications on the firm value. Based on panel data of 73 companies that listed in Indonesian Stock Exchange, the results of research using Eviews 10 version application as follows: Institution ownership has positive dan significant influenced on dividend policy. However, cash dividend tax has negative influence on dividend policy insignificantly and retained earnings has positive and insignificant influenced on dividend policy. Cash dividend tax, institution ownership and retained earning together have significant influence on dividend policy. Cash dividend tax has positive and significant influence on firm value. Institution ownership and retained earnings have negative and significant influence on firm value. Cash dividend tax, institution ownership, retained earnings, dividen policy have significant influence on firm value. Cash dividend tax, institutional ownership, dan retained earnings have direct connection on firm value while dividend payout ratio fails to be as intervening variable on firm value. Keywords: Cash dividend tax, institutional ownership, retained earnings, dividend policy, firm value JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8036